Point-defect-optimized electron distribution for enhanced electrocatalysis: Towards the perfection of the imperfections. (April 2020) - Jiao, Shilong; Fu, Xianwei; Zhang, Li; Zeng, Yu-Jia; Huang, Hongwen
Graphical abstract: Highlights: In-depth understanding of the defect-induced alteration of the electronic structures during the electrocatalytic process. Physics/chemistry that lies behind the advanced characterization methods for the investigation of defects are discussed. Summarize the recent progress on the defect-optimized electrocatalyst based on the dimension of the imperfections. Present the major challenges and opportunities in the defect engineering for the rational design of electrocatalysts. Abstract: Conflicts between the limited energy resources and the continuingly growing demand of the industry accompanied by worsening climate change have pushed the development of energy storage and conversion devices to the center of the research society. Electrocatalysis, which converts chemical energy and electricity to one another, has emerged as a potential solution for providing affordable clean energy and alleviating the environmental crisis. Defects with zero to three dimensions, which can intrinsically influence the electronic structure of the electrocatalysts and its interaction with the surrounding environment, has made the rational design and preparation of electrocatalysts with high activity, long-term stability and acceptable Faradaic efficiency be readily guaranteed. Here, we review the significant role of the defects in selected electrocatalytic processes based on the understanding of the link between the physics and chemistry of the defects. After a background introduction, we give a brief discussion of the formation process of the defects, along with the emerging preparation methods to generate imperfections in the electrocatalysts. Furthermore, a basic-theory-and-practice-combined introduction of the advanced characterization methods for the identification and analysis of defects will be presented. Next, we focus on the recent progress that has been achieved in developing efficient defect-featured electrocatalysts in a wide range of electrocatalytic processes. Finally, we conclude the challenges and opportunities in this promising and thriving field from our perspective.